The mental health of expeditionary women in Antarctica: A systematic review - Mayra Gabriela Machado deSouza; Jairo Werner Junior (Mental Health Science)
Abstract Antarctica is considered an isolated, confined, and extreme environment. Expeditionary members' health conditions deserve special attention in such environments since access to healthcare is difficult and social networks are limited. Women in Antarctica not only are a minority recently integrated into a predominantly male setting, but also need to withstand the environment's influence and demonstrate emotional intelligence, physical capacity, and intellectual competence to share this environment, which does not always provide structures adapted to their daily needs. Our objective was to analyze quantitative evidence on the health of expeditionary women in Antarctica. This is a systematic review of the narrative synthesis type, consulting the principal databases. The inclusion criteria were quantitative, observational studies with measures of mental disorders during expeditions on the frozen continent or after conclusion of the missions. Exclusion criteria were review studies and studies that only included men. Results: We retrieved 1865 publications and included 43 in the review that contained specific results for expeditionary women (n = 7); results of expeditionary crews of both sexes but reported without specification by gender (n = 25); and results pertaining to expeditionary members reported by terms that prevented specification by gender (n = 11). The literature is inconsistent on the mental health of expeditionary women in isolated, confined, and extreme environments. Even so, the review showed that women appear to be more prone to manifesting depressive symptoms and that gender appears to influence sleep quality. More studies are needed that specify the psychological alterations developed by women in Antarctica.